Section style in the poetry of Omar bin Abi Rabia (Journal of Humanities and Social Sciences Research, 2023)
The research is concerned with studying the oath style in the poetry of the Umayyad ghazal poet Umar ibn Abi Rabi’ah al-Makhzoumi, which is one of the methods of non-demanding composition whose forms are frequently cited in both Arabs and their poetry, because of its strength and elegance in emphasizing and consolidating speech, and we found evidence in its different form in the poetry of Umar ibn Abi Rabia, as more than employing it in his poetry in a way that enhances his poetic purposes and gives his meanings confirmation and elegance in different places, so we dealt with it by analysis and study and showed its impact on the meanings and purposes of the poet and its role in influencing the recipient through research in its structures and connotations by studying the sentence of the oath with its types, the tools of the oath and the sentence The oath and the letters that fall in it, such as (lam), and it examines the deletion, repetition, and the meeting of the condition with the oath, and the semantic value of all these transformations in the poet's poetry.